(3GdfHjd Edi fMh GdJSgjds - (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO , J (B905 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3eMeO UGdM Hf eMeO GdQGYj s)
(3ChdgG (B:s
(3hHYO, abO SCdfj CjgG GdCN GdaGVd Cf CTQM dc cJGH GdJSgjd Ydi hLg GdEjVGM hGdJSgjd s
(3BNQgG (B:s
(3hgGJGf GdeSCdJGf eHfjJGf Ydi Cf GdeHJOC ZjQ GdNHQ hGdUaI ZjQ eQahYI ced eG hLO ef gPG GdTQM GdeHGQc s
(3HgG fXGe GdJYbjHIs
(3cJHJ Yf fSNI HNW GdeDda GdecJhHI SfI (B892 (3g` GfXQ OGNd GdeNWhWI U (B279s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs